Analysis of factors influencing variation in soil respiration between forest types : a case study at Bukit Timah Nature Reserve - Chua, Terence Jie (Nanyang Technological University, 2020)
Tropical forests have been facing rapid degradation in recent decades, which alters pristine primary forest into secondary forests. Despite there being increasing portions of secondary forests, few studies are explaining how rapid degradation of pristine forests influences carbon balance and dynamics in a tropical forest. Here we studied the spatial patterns of soil respiration, which is a crucial process influencing terrestrial carbon balance. Our experiment was conducted at 100 measurement locations within a primary and secondary tropical rainforest in Bukit Timah Nature Reserve, Singapore. We aimed to investigate whether soil respiration rates differed between both forest types, and what the underlying abiotic and biotic factors influencing the differences were. We hypothesize that the soil respiration rates in the secondary forest would be higher than that of the primary forest, and that the factors we analyzed positively influence soil respiration rates. Results showed that the soil respiration rates observed in the secondary forest was higher than that of the primary forest. However, none of the tested factors (soil temperature, soil moisture, diameter of trees at breast height, canopy cover) were significantly influencing soil respiration rates. Our findings suggest that the factors tested in our study were not crucial in governing spatial pattern of soil respiration at our site and that other factors such as soil organic carbon content and species composition are more important factors influencing spatial variation of soil respiration between primary and secondary tropical forests.